A Ghostly Aside: Reviewing and Remembering the “Forgotten” 1918-1919 Spanish Flu Pandemic in Newfoundland and Labrador - Chafe, Ryan R. (Newfoundland and Labrador Studies, 2023)
The current COVID-19 crisis emphasizes that pandemics are both biomedical phenomena and significant multifaceted historical events. The 1918–19 Influenza Pandemic, known as the “Spanish Flu,” was estimated to have killed between fifty to one hundred million people, yet historians like Alfred Crosby labelled the Spanish Flu a “forgotten” pandemic because of its absence from contemporary and academic writing. Memory of the pandemic has recently received academic attention in Pandemic Re-Awakenings (2022) though memories of thepandemic in Newfoundland and Labrador (NL) were not explored in that work. This paper examines the memory of Spanish Flu in NL using both “global” and “local” perspectives and argues for the importance of applying globally recognized academic theory, methodology, and examples to local perspectives and experiences. During an era fixated on remembrance, the pandemic dead were concealed by the Great War, except members of the community who fit into heroic narratives. Without utilitarian value, the memory of the Spanish Flu was “forgotten,”an active and passive process that downplayed its impact on human society. Memory of the Spanish Flu persisted in private form and influenced the world through public health policy changes and as a precedent-setting event to be viewed in grim anticipation of future pandemics.